Makna Mengampuni Studi Eksegetis Matius 18:21-22 dan Relevansinya terhadap Kehidupan Kristen Saat Ini - Frans Mardohar Parulian Lumbantobing; Supriadi Siburian (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to find out and provide an overview of the meaning of forgiveness according to Matthew 18:21-22 and its relevance to the Christian life today. The method used in this study is qualitative research with a library research approach, which is a biblical study, especially the New Testament from content analysis. The interpretation method used is a combination of the interpretations of Stevri Indra Lumintang, Gordon D Fee, and Sugiyono. Jesus' teaching on forgiveness is limitless. In accordance with the formulation of the problem that the author has written, it is about why it is so difficult to give forgiveness to people who have wronged us. Therefore, forgiveness according to Jesus in Matthew 18:21-35 is very important in connection with the life of the believer. The purpose of this study is so that the foundation laid by Jesus in relation to forgiveness becomes a pattern of believer's life. Believers are motivated in order to realize the forgiveness taught by Jesus. God's forgiveness in Jesus Christ is based on God's mercy. Everyone who believes in Jesus receives forgiveness from God by God's great mercy. Jesus taught every believer to forgive for having received God's mercy. This attitude needs to be taken and applied by every believer who has received forgiveness from God in Jesus Christ.